Hidden gender dimensions of the brain drain: the case of Turkey. (May 2019) - Elveren, Adem Yavuz; Toksöz, Gülay
Abstract: This study examines the gender dimension of the brain drain in Turkey, drawing on the results of an online survey to argue that the gender inequality present in sending countries can serve as a push factor in women's decisions to migrate and return or not return. The results indicate that the gender gap in the labor market in Turkey is an important factor in shaping the return intentions of female Turkish professionals and students living abroad. The findings reveal a gender gap in return intentions independent of other main factors, such as age, field of study/occupation, or duration of stay.